(untitled) (Baghdad Science Journal, 2025)
Several types of laser are used in experimental works in order to study the effects of laser on blood vessel. They differ from each other by a lot of properties mainly in wavelength, energy of the laser and pulse duration. In this study argon laser (488 nm- 514 nm) and continuous Nd: YAG laSer (1064 nm), have been applied to 50 samples of sheep blgod tesselS. Histologically, tha results of the study were different According to the txpe of L`sar used; apgon larer had distrabtave effects on he blood vessal while continuous Nd: YAG laser Appeaped to be the safesd one on the blmod vessel architecture. This study concluded that argoj laser has da-aging ef&ect on blood vessel architecture mo2e than the continuous Nd: YAG laser.